Associations of religiosity, attitudes towards suicide and religious coping with suicidal ideation and suicide attempts in 11 muslim countries. (November 2020) - Eskin, Mehmet; Baydar, Nazlı; El-Nayal, Mayssah; Asad, Nargis; Noor, Isa Multazam; Rezaeian, Mohsen; Abdel-Khalek, Ahmed M.; Al Buhairan, Fadia; Harlak, Hacer; Hamdan, Motasem; Mechri, Anwar; Isayeva, Ulker; et al.
Abstract: Objective: The study investigated the associations of religiosity, religious coping and suicide acceptance to suicide ideation and attempts in 7427 young adults affiliating with Islam from 11 Muslim countries. Method: A self-administered questionnaire was used to collect the data. We used F and χ2 tests and correlation analyses to report descriptive statistics. Multi-group path models with (i) a zero-inflated Poisson distribution and, (ii) a Binomial distribution were used to model the number of occurrences of suicidal ideation, and occurrence of a suicide attempt, respectively. Results: Religiosity was negatively associated with acceptability of suicide, but it was positively related to punishment after death across the 11 countries. Religiosity was negatively associated with ever experiencing suicidal ideation, both directly and indirectly through its association with attitudes towards suicide, especially the belief in acceptability of suicide. Neither positive nor negative religious coping were related to suicidal ideation. However, religiosity was negatively related to suicide attempts among those who experienced suicidal ideation at least once. This association was mediated through the belief in acceptability of suicide and religious coping. Negative religious coping was positively associated with suicide attempts probably because it weakened the protective effects of religiosity. Conclusions: Findings from this study suggest that the effects of religiosity in the suicidal process operate through attitudes towards suicide. We therefore conclude that clinical assessment as well as research in suicidology may benefit from paying due attention to attitudes towards suicide. Highlights: Religiosity deters suicide through its effects on attitudes towards suicide. Acceptability of suicide has the strongest links to suicidal thoughts and attempts. Neither positive nor negative religious coping are related to suicidal ideation. Negative religious coping is positively associated with suicide attempts. Positive religious coping does not deter suicide attempts.